2020
DOI: 10.1136/bmjopen-2019-034245
|View full text |Cite
|
Sign up to set email alerts
|

Severe varicose veins and the risk of mortality: a nationwide population-based cohort study

Abstract: ObjectiveVaricose veins (VVs) are common and although considered benign may cause morbidity. However, the association between VV severity and cardiovascular and mortality risks remains unknown. The aim of this study was to investigate the factors associated with overall mortality in patients with VV.MethodsA total of 4644 patients with newly diagnosed VV between 1999 and 2013 were identified from Taiwan’s National Health Insurance Database. VV severity was classified from grade 1 to 3 according to the presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
16
0
3
Order By: Relevance
“…Other cross-sectional studies also indicate that peripheral arterial disease and cardiovascular disorders were associated with an increased risk of vascular dementia ( Newman et al, 2005 ; Laurin et al, 2007 ). The presence of varicose veins is related to an increased risk of cardiovascular events and mortality ( Wu et al, 2020 ). Varicose veins might induce inflammation ( Markovic and Shortell, 2013 ) and endothelial dysfunction ( Komarów et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cross-sectional studies also indicate that peripheral arterial disease and cardiovascular disorders were associated with an increased risk of vascular dementia ( Newman et al, 2005 ; Laurin et al, 2007 ). The presence of varicose veins is related to an increased risk of cardiovascular events and mortality ( Wu et al, 2020 ). Varicose veins might induce inflammation ( Markovic and Shortell, 2013 ) and endothelial dysfunction ( Komarów et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormones produced by visceral fat might play a role in cognitive function decline ( Nota et al, 2020 ). Varicose veins presence is a risk factor for cardiovascular events and mortality ( Wu et al, 2020 ). Varicose veins might induce inflammation ( Markovic and Shortell, 2013 ) and endothelial dysfunction ( Komarów et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Virchow's triad, consisting of endothelial damage, hypercoagulability, and stasis, plays a significant role in the etiopathogenesis of venous thromboembolism. Venous stasis is expected in patients with varicose veins, especially in those with dense pacts, which predisposes to thromboembolic events [15].…”
Section: Discussionmentioning
confidence: 99%
“…Factors involved in the formation of varicose veins cause the remodeling of the vascular wall, the destruction and failure of the venous valves. With the inclusion of leukocytemediated inflammation, it may cause endothelial dysfunction, edema, ulcers and, in advanced stages, deep vein thrombosis [15]. All these events cause an increase in thrombocyte volume, a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns were echoed in a large population‐based study carried out by Prochaska et al ., who found that the higher CEAP score was associated with a higher ‘predicted 10‐year risk for incident cardiovascular disease’ 37 . These findings suggest that long‐term cardiovascular monitoring of patients with CVI is needed 36,37 …”
Section: Chronic Venous Disease and Major Adverse Cardiovascular Eventsmentioning
confidence: 99%